Preliminary In Vitro and In Vivo Evaluation of Antidiabetic Activity of Ducrosia anethifolia Boiss. and Its Linear Furanocoumarins - Nagwa M. M. Shalaby (BioMed Research International, 2014)
Aim. Ducrosia anethifolia is used as flavoring additive. There have been little detailed phytochemical reports on this genus and the antidiabetic activity of this plant is not yet evaluated. Method. Structure of compounds was deduced by spectroscopic analyses. Preliminary in vitro evaluation of the antidiabetic activity of crude extract and its furanocoumarins was carried out (α-amylase, α-glucosidase, and β-galactosidase). The in vivo activity was investigated by measuring some oxidative stress markers. Biomarkers of liver injury and kidney were also determined. Results. Eight linear furanocoumarins, psoralen, 5-methoxypsoralen, 8-methoxypsoralen, imperatorin, isooxypeucedanin, pabulenol, oxypeucedanin methanolate, oxypeucedanin hydrate, and 3-O-glucopyranosyl-β-sitosterol, were isolated. All compounds were reported for the first time from the genus Ducrosia except pabulenol. The blood glucose level, liver function enzymes, total protein, lipid, and cholesterol levels were significantly normalized by extract treatment. The antioxidant markers, glucolytic, and gluconeogenic enzymes were significantly ameliorated and the elevated level of kidney biomarkers in the diabetic groups was restored. The compounds showed inhibitory activity in a concentration dependant manner. Imperatorin and 5-methoxypsoralen showed the most potent inhibiting power. Conclusion. D. anethifolia extract showed hypoglycemic, hypolipidemic, and antioxidant effect as well as ameliorating kidney function. This extract and some linear furanocoumarins exhibited carbohydrate metabolizing enzymes inhibitory effect.